1999
DOI: 10.1046/j.1365-2958.1999.01583.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for Rev1p and Rev7p during translesion synthesis in Saccharomyces cerevisiae

Abstract: SummaryTranslesion synthesis (TLS) in Saccharomyces cerevisiae requires at least Rev1p and polymerase z (Pol z), a complex of the Rev3 polymerase and its accessory factor Rev7p. Although their precise role(s) are poorly characterized, in vitro studies suggest that each protein contributes to TLS in a manner dependent on the particular lesion and surrounding DNA sequence. In the present study, strand segregation analysis is used to attempt to identify the role(s) of the Rev1 and Rev7 proteins during TLS. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
48
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 43 publications
4
48
0
Order By: Relevance
“…4). Among the four mutants recovered, three were the expected Ϫ1G; the remaining mutant was an untargeted Ϫ1C (previously observed in this sequence context in E. coli [21] and yeast [4]). Interestingly, the four mutants recovered were identified in SSA as being mixed (3G and 3Gϩ3 positive [ Fig.…”
Section: Methodssupporting
confidence: 55%
See 2 more Smart Citations
“…4). Among the four mutants recovered, three were the expected Ϫ1G; the remaining mutant was an untargeted Ϫ1C (previously observed in this sequence context in E. coli [21] and yeast [4]). Interestingly, the four mutants recovered were identified in SSA as being mixed (3G and 3Gϩ3 positive [ Fig.…”
Section: Methodssupporting
confidence: 55%
“…The strategy used to construct plasmids containing a single AAF adduct on the 3Ј guanine of the sequence 5Ј GGG 3Ј, itself located within a sequence heterology, involved the formation of gapped-duplex molecules described previously (19). The only modification was that the resulting adduct-containing heteroduplex plasmids were treated with Plasmid-Safe ATP-dependent DNase (Epicentre Technologies) after recovery from CsCl gradients in order to eliminate contaminating linear, double-stranded, homoduplex DNA which can transform yeast, albeit with a lower efficiency than that of closed, circular molecules (4,39). Potential contamination by undigested pKBL(Helper) plasmids was minimized by HincII digestion prior to DNase treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polζ is not essential for cell viability in yeast while disruption of REV3 in mice causes embryonic lethality [4]. In vitro, Polζ acts mainly as a mispaired primer extender (frequency 10 −1 −10 −2 ), although it can also incorporate nucleotides opposite a DNA lesion.Polζ requires the Rev1 protein, which is indispensable for UV mutagenesis [4][5][6][7][8] and for mutagenesis resulting from TLS occurring through AP sites [9] and other damaged bases [10]. Rev1 is a member of the Y family of DNA polymerases, and specifically incorporates C opposite all template bases or AP sites [4,9].…”
mentioning
confidence: 99%
“…For example, even though both Pol and Rev1 are required for UV mutagenesis resulting from the action of Pol at the extension step of TLS through UV lesions, the Rev1 DNA polymerase activity is not required (28). Instead, Rev1 performs a structural role in modulating Pol function in TLS (5,9,24). In keeping with such a structural role for Rev1, we have shown that Rev1 forms a stable complex with Pol and that this complex formation requires the binding of the Rev1 C terminus with the polymerase domain of Rev3 (2).…”
mentioning
confidence: 99%